Smith-Lemli-Opitz syndrome: A pathophysiological manifestation of the Bloch hypothesis - Chattopadhyay, Amitabha; Sharma, Ashwani (Frontiers in Molecular Biosciences, 2023)
The biosynthesis of cholesterol, an essential component of higher eukaryotic membranes, was worked out by Konrad Bloch (and Feodor Lynen) in the 1960s and they received the Nobel Prize around that time in recognition of their pioneering contributions. An elegant consequence of this was a hypothesis proposed by Konrad Bloch (the Bloch hypothesis) which suggests that each subsequent intermediate in the cholesterol biosynthesis pathway is superior in supporting membrane function in higher eukaryotes relative to its precursor. In this review, we discuss an autosomal recessive metabolic disorder, known as Smith-Lemli-Opitz syndrome (SLOS), associated with a defect in the Kandutsch-Russell pathway of cholesterol biosynthesis that results in accumulation of the immediate precursor of cholesterol in its biosynthetic pathway (7-dehydrocholesterol) and an altered cholesterol to total sterol ratio. Patients suffering from SLOS have several developmental, behavioral and cognitive abnormalities for which no drug is available yet. We characterize SLOS as a manifestation of the Bloch hypothesis and review its molecular etiology and current treatment. We further discuss defective Hedgehog signaling in SLOS and focus on the role of the serotonin1A receptor, a representative neurotransmitter receptor belonging to the GPCR family, in SLOS. Notably, ligand binding activity and cellular signaling of serotonin1A receptors are impaired in SLOS-like condition. Importantly, cellular localization and intracellular trafficking of the serotonin1A receptor (which constitute an important determinant of a GPCR cellular function) are compromised in SLOS. We highlight some of the recent developments and emerging concepts in SLOS pathobiology and suggest that novel therapies based on trafficking defects of target receptors could provide new insight into treatment of SLOS.